Harmonic enhancement in microgrid with applications on sensitive loads - Montaser Hafez; Hussein El-Eissawi; Nabil Ayad (Institute of Advanced Engineering and Science, 2019)
Power quality issues are an important and growing problem in microgrid. There are two reasons; the more active consumer is participating in the power sector, the use of renewable energy which having a great impact on voltage variation. This paper discusses power quality disturbance and especially harmonic distortion issues in microgrid, and suggests a solution to maintain the operation of the distribution system within power quality standard. To protect sensitive loads from harmonics produced by the grid and by renewable energy sources, passive harmonic filter has been proposed in this paper. The electrical system of a nuclear research reactor as sensitive loads is designed by using Electrical Transient Analyzer Program (ETAP) software. The results show these technical issues are presented with their influence on electrical voltage and harmonic specter.